2017
DOI: 10.5185/amlett.2017.1577
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan bio-functionalization of carbon nanotube arrayed electrode

Abstract: Nanostructured electrodes enable a new generation of electrochemical sensors by increasing their surface area that lead to stronger signals generated by electrochemically-active molecules, such as diagnostic redox-active biomarkers. Yet, the selectivity of these translational sensors is far from being sufficient for discriminating between individual molecules in multicomponent samples, such as biofluids. Here, we propose an approach to improve the selectivity of nanostructured electrodes using a simple modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…162,175 Common methods, including wrapping of conjugated biopolymers like DNA or chitosan, furthermore enhanced solubilization of the nanotube, thus decreased agglomeration effects and promoted biocompatibility. 115,166,176 Yet, studies like Fujigaya et al also accounted for rather low coating stabilities and described the impact and structure of so generated coronas as fairly unpredictable entailing comprehensive screening studies and specificity tests before use. 175 An example of this can be seen by nanotube modification via nucleic acid polymer wrapping by Kruss et al which was found to exert increased nIR fluorescence intensity in the presence of specific catecholamines, particularly dopamine and epinephrine, and likewise defines the primary sensor model of this thesis.…”
Section: Functionalization Methods and Recognition Strategies Of Swcntsmentioning
confidence: 99%
“…162,175 Common methods, including wrapping of conjugated biopolymers like DNA or chitosan, furthermore enhanced solubilization of the nanotube, thus decreased agglomeration effects and promoted biocompatibility. 115,166,176 Yet, studies like Fujigaya et al also accounted for rather low coating stabilities and described the impact and structure of so generated coronas as fairly unpredictable entailing comprehensive screening studies and specificity tests before use. 175 An example of this can be seen by nanotube modification via nucleic acid polymer wrapping by Kruss et al which was found to exert increased nIR fluorescence intensity in the presence of specific catecholamines, particularly dopamine and epinephrine, and likewise defines the primary sensor model of this thesis.…”
Section: Functionalization Methods and Recognition Strategies Of Swcntsmentioning
confidence: 99%